Exile and Social Thought : Hungarian Intellectuals in Germany and Austria, 1919-1933. - Congdon, Lee. (Princeton : Princeton University Press, 2014)
Embroiled in the political events surrounding World War I and the failed Hungarian revolutions of 1918-19, a number of intellectuals fled Hungary for Germany and Austria, where they essentially created Weimar culture. Among them were Georg Lukács, whose History and Class Consciousness recast Marxism and challenged even those who repudiated its politics; Bela Balázs, who pioneered film theory and collaborated with film-makers G.W. Pabst, Leni Riefenstahl, and Alexander Korda; László Moholy-Nagy, who codirected the Bauhaus during its heyday in the mid-1920s; and Karl Mannheim, whose Ideology.
List of Illustrations ; Preface ; Acknowledgments ; INTRODUCTION: Hungarian Intellectuals in War and Revolution, 1914-1919; PART ONE: THE COMMUNISTS; ONE; Georg LukÁcs: The Road to Lenin; TWO ; BÉla BalÁzs: The Road to the Party; PART TWO: THE AVANT-GARDE; THREE; Lajos KassÁk: The Ma Circle; FOUR ; LÁszlÓ Moholy-Nagy: The Bauhaus; PART THREE: THE LIBERALS; FIVE; Aurel Kolnai: The Path to Rome; SIX; Karl Mannheim: The Sociology of Knowledge; CONCLUSION; Community and Consciousness; NOTES; BIBLIOGRAPHY; INDEX.
Print version record.
eBooks on EBSCOhost
Keywords: Intellectuals -- Hungary -- History -- 20th century; Intellectuals -- Germany -- History -- 20th century; Intellectuals -- Austria -- History -- 20th century; Exiles -- Hungary -- History -- 20th century; Exiles -- Germany -- History -- 20th century; Sociology -- Hungary -- History -- 20th century; Sociology -- Germany -- History -- 20th century; Sociology -- Austria -- History -- 20th century; Exiles -- Austria -- History -- 20th century; Intellectuels -- Hongrie -- Histoire -- 20e siècle.; Intellectuels -- Allemagne -- Histoire -- 20e siècle.; Intellectuels -- Autriche -- Histoire -- 20e siècle.; Sociologie -- Hongrie -- Histoire -- 20e siècle.; Sociologie -- Allemagne -- Histoire -- 20e siècle.; Sociologie -- Autriche -- Histoire -- 20e siècle.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Modern -- 20th Century; Exiles; Intellectuals; Sociology; Austria; Germany; Hungary; 1900-1999; Electronic books; History